Memory, credibility and insight: How video-based feedback promotes deeper reflection and learning in objective structured clinical exams. (3rd June 2022) - Makrides, Alexandra; Yeates, Peter
Abstract: Introduction: Providing high-quality feedback from Objective Structured Clinical Exams (OSCEs) is important but challenging. Whilst prior research suggests that video-based feedback (VbF), where students review their own performances alongside usual examiner feedback, may usefully enhance verbal or written feedback, little is known about how students experience or interact with VbF or what mechanisms may underly any such benefits. Methods: We used social constructive grounded theory to explore students' interaction with VbF. Within semi-structured interviews, students reviewed their verbal feedback from examiners before watching a video of the same performance, reflecting with the interviewer before and after the video. Transcribed interviews were analysed using grounded theory analysis methods. Result: Videos greatly enhanced students' memories of their performance, which increased their receptivity to and the credibility of examiners' feedback. Reflecting on video performances produced novel insights for students beyond the points described by examiners. Students triangulated these novel insights with their own self-assessment and experiences from practice to reflect deeply on their performance which led to the generation of additional, often patient-orientated, learning objectives. Conclusions: The array of beneficial mechanisms evoked by VbF suggests it may be a powerful means to richly support students' learning in both formative and summative contexts.